Validation of the Asia-Pacific colorectal screening score and its modified versions in predicting colorectal advanced neoplasia in Chinese population - Kong, Yunxin; Zhuo, Lin; Dong, Dong; Zhuo, Lang; Lou, Peian; Cai, Ting; Chen, Siting; Pan, Jianqiang; Gao, Yihuan; Lu, Hang; Ma, Yue; Dong, Zongmei; et al. (BMC cancer, 2022)
Colorectal cancer is one of the most common cancers in the world. Several studies suggest using the Asia-Pacific colorectal screening (APCS) score and its modified versions to select high-risk populations for early colonoscopy, but external validation remains rare, and which score should be selected for CRC screening in China is unclear. Validation of multiple scores in the same population might help to choose the best performing score. We conducted a cross-sectional study under the framework of Cancer Screening Program in Urban China, data from asymptomatic colorectal cancer screening in Xuzhou was used to validate the APCS score, the colorectal neoplasia predict (CNP) score, the Korean colorectal screening (KCS) score, the Modified APCS score and the 8-point risk score in predicting colorectal advanced neoplasia (CAN). 1804 subjects were included in the analysis and 112 CAN (6.21%) was detected. In each score, the detection rate of CAN was higher in the high-risk group than in the non-high-risk group (P < 0.05), and the RR (95%C.I.) ranged 2.20 (1.50-3.22) [8-point risk] to 4.00 (2.41-6.65) [Modified APCS]. The c-statistics (95%C.I.) of the scoring systems ranged from 0.58 (0.53-0.62) [8-point risk] to 0.65 (0.61-0.69) [KCS]. The sensitivity (95%C.I.) of these systems ranged from 31.25 (22.83-40.70) [8-point risk] to 84.82 (76.81-90.90) [Modified APCS], while the specificity (95%C.I.) ranged from 43.50 (41.12-45.90) [Modified APCS] to 83.81 (81.96-85.53) [8-point risk]. Using the APCS scoring system as a comparator, the net reclassification improvement (NRI) of each modified version ranged from - 10.34% (95%C.I.: - 22.63 to 1.95%) [8-point risk] to 4.79% (95%C.I.: - 1.50% to 11.08) [KCS]. The colonoscopy resource load (95%C.I.) ranged from 9 [1-3] [8-point risk] to 11 [3-5] [APCS and Modified APCS]. The APCS score and its modified versions have certain ability to predict the risk of advanced neoplasia and reduce the resource load. The modified APCS score and the KCS score seemed the preferable systems to classify high risk subjects based on its high RR, sensitivity and predictive ability in the selected population. Future research could focus on adding risk factors or combining with laboratory test results to improve the predictive power of the scoring system.